2022
DOI: 10.1051/0004-6361/202244345
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the accuracy of asteroseismic mass and radius estimates of giant stars

Abstract: Context. Eclipsing binary stars with an oscillating giant component allow accurate stellar parameters to be derived and asteroseismic methods to be tested and calibrated. To this aim, suitable systems need to be firstly identified and secondly measured precisely and accurately. KIC 4054905 is one such system, which has been identified, but with measurements of a relatively low precision and with some confusion regarding its parameters and evolutionary state. Aims. Our aim is to provide a detailed and precise c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…By applying this f Δν -corrected scaling relation, it was found that the radii align more closely with Gaia radii within 2% (Zinn et al 2019). Moreover, the masses now agree with dynamical masses within observational uncertainties (Brogaard et al 2018(Brogaard et al , 2022. On the other hand, based on the mixing-length theory of convection and results from nonadiabatic calculations of mode excitation and damping, Belkacem et al (2011Belkacem et al ( , 2013 suggested that the max n scaling relation should depend on Mach number near the stellar surface.…”
Section: Introductionmentioning
confidence: 67%
“…By applying this f Δν -corrected scaling relation, it was found that the radii align more closely with Gaia radii within 2% (Zinn et al 2019). Moreover, the masses now agree with dynamical masses within observational uncertainties (Brogaard et al 2018(Brogaard et al , 2022. On the other hand, based on the mixing-length theory of convection and results from nonadiabatic calculations of mode excitation and damping, Belkacem et al (2011Belkacem et al ( , 2013 suggested that the max n scaling relation should depend on Mach number near the stellar surface.…”
Section: Introductionmentioning
confidence: 67%
“…To test the accuracy of the scaling relations after applying corrections for various effects, we used a sample of five red giants in eclipsing binary systems, whose masses and radii are accurately measured by dynamical modeling. The five red giants are KIC 8410637 (Frandsen et al 2013), KIC 9970396, KIC 7037405, KIC 9540226 (Brogaard et al 2018, and KIC 4054905 (Brogaard et al 2022). They all have resolution spectra from APOGEE, allowing us to use the corrected scaling relations for APOGEE data.…”
Section: Modeling-based Scaling Relationsmentioning
confidence: 99%
“…This method makes use of three equations representing the independent observations: The Stefan-Boltzmann equation for the luminosity and the two independent asteroseismic scaling relations for ρ and g A23, page 10 of 21 (e.g. Brogaard et al 2022, and references therein):…”
Section: Masses and Radii Of The Giantsmentioning
confidence: 99%